2004
DOI: 10.3184/147020604783637462
|View full text |Cite
|
Sign up to set email alerts
|

Avian egg antibodies: basic and potential applications

Abstract: The existence of an IgG-like molecule in avian eggs, referred to as IgY, has been well documented, and extensive research has been carried out on its characterization, production and purification. Although it is the functional equivalent of mammalian IgG, the major serum antibody found in mammals, IgY is structurally different, and has been found to exhibit several important differences when compared to mammalian antibodies, including its physico-chemical properties and immunological capabilities. Recently, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(36 citation statements)
references
References 172 publications
(177 reference statements)
3
32
0
1
Order By: Relevance
“…The results indicated that anti-NANOS2 IgY antibody showed the better affinity and specific reactivity to the rNANOS2 protein of dairy goat origin than anti-NANOS2 antibodies got from rabbit. It is extensively reported that chicken antibodies could bind to more epitopes on a mammalian protein than the corresponding mammalian antibodies and the absence of immunological cross-reactivity between chicken IgY and mammalian IgG was determined by the evolution divergence (Hadge and Ambrosius 1984;Kovacs-Nolan and Mine 2004;Dias da Silva and Tambourgi 2010). These findings strongly support the application of anti-NANOS2 IgY as a research tool to explore the biological functions of NANOS2 protein in male germ cell development.…”
Section: Controlsupporting
confidence: 59%
See 1 more Smart Citation
“…The results indicated that anti-NANOS2 IgY antibody showed the better affinity and specific reactivity to the rNANOS2 protein of dairy goat origin than anti-NANOS2 antibodies got from rabbit. It is extensively reported that chicken antibodies could bind to more epitopes on a mammalian protein than the corresponding mammalian antibodies and the absence of immunological cross-reactivity between chicken IgY and mammalian IgG was determined by the evolution divergence (Hadge and Ambrosius 1984;Kovacs-Nolan and Mine 2004;Dias da Silva and Tambourgi 2010). These findings strongly support the application of anti-NANOS2 IgY as a research tool to explore the biological functions of NANOS2 protein in male germ cell development.…”
Section: Controlsupporting
confidence: 59%
“…The phylogenetic distance between mammals and chickens renders more advantage for the preparation of antibodies in chickens against a wide range of highly conserved mammalian proteins (Kovacs-Nolan and Mine 2004). Hence, the present study was aimed at preparing the chicken immunoglobulin Y (IgY) against recombinant NANOS2 RNA binding protein of dairy goat origin and comparing the similarity and difference between the NANOS2 of mice and dairy goat origin using bioinformatics tools to identify the difference in antigenic determinants.…”
Section: Doi: 1017221/8129-cjasmentioning
confidence: 99%
“…Testing has revealed that IgY has a high success rate against several enteric pathogens, including bovine and human rotaviruses, enterotoxigenic Escherichia coli (ETEC), Edwardsiella tarda, bovine coronavirus, Yersinia ruckeri, Salmonella spp., Staphylococcus and Pseudomonas when administered orally. When investigated in vitro, IgY was shown to preclude infection and also to limit growth, while in animals it was observed to inhibit the symptoms of infection (Kovacs-Nolan & Mine, 2004). stability and neutralization efficacy" (Srisapoome, Punyokun, Hongprayoon, & Areechon, 2006;Punyokun, Hongprayoon, Srisapoome, & Sirinarumitr, 2013), we found that the activity of IgY was destroyed under gastric conditions which contained pepsin or a low pH value.…”
Section: Introductionmentioning
confidence: 91%
“…The heavy chain has four constant domains and one variable domain. The molecular weight of IgY is about 180 kDa [40]. One hen generally lays about 290 eggs per year which represents 5 kg of yolk.…”
Section: Immunoglobulin Ymentioning
confidence: 99%